La grammaire au lycée…qu’en est-il des pratiques de classe ? - Idjet, Ahlem (Journal of Human Sciences, 2016)
In this article, we are interested in the practices of grammatical teaching adopted by the teachers of French as a foreign language. The objective of the analysis of the filmed sessions of teaching is to have on one hand a better understanding of the practices of teaching of the grammar in the secondary school, and on the other hand, to observe if the didactic proposals stemming from the enunciative grammar are applied in class of French.